Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2023)
A dataset listing the 1 species recorded in GBIF matching the query: { "and" : [ "BasisOfRecord is Human Observation", "Country is one of (United States of America, Canada, Svalbard and Jan Mayen, Greenland, Russian Federation)", "HasCoordinate is true", "HasGeospatialIssue is false", "TaxonKey is Ursus maritimus Phipps, 1774", "Year 1900-2023" ] } The dataset's 1 records were derived from 23 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0108380-230224095556074/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences